Towards a more meaningful financial statement / Wee Shu Hui - Wee, Shu Hui (Institut Teknologi Mara Cawangan Sarawak, 1989)
Private enterprise companies have social and environmental responsibilities to employees, customers and the community. A measurement such as earnings per share is much too narrow and restricted to the proprietal interests only. Very often, profitability, which seems to dominate the business world, is emphasised so much that it overshadows the social responsibility of corporate organisations. Every company is required to prepare annual financial statements. Section 169 of the Malaysia Companies Act provides that the directors of every company must, in respect of each accounting period of the company, prepare a profit and loss account and a balance sheet as at the date at which any profit and loss statement is made up. Reports of the directors and auditors should be attached to the two financial statements. The financial statements are quantified statements attempting to convey to the users as to what was happening in the financial accounting year. At present, the usefulness of financial statements in fulfilling the users’ needs is restricted because of the defects of measurement used. In times of escalating inflation, historical cost accounting fails to depict a true picture to the users. When reported figures are not related to current values, there may be over or understatement of performance as measured by profits and returns on assets.